HIV epidemic among drug users in China: 1995–2011. (January 2015) - Wang, Lan; Guo, Wei; Li, Dongmin; Ding, Zhengwei; McGoogan, Jennifer M.; Wang, Ning; Wu, Zunyou; Wang, Lu
Abstract: Aim: To describe trends in the HIV epidemic among drug users (DUs) in China from 1995 to 2011. Design, Setting and Participants: Data sets from China's national HIV/AIDS case reporting and sentinel surveillance systems as of December 2011 were used separately for descriptive analysis. Measures: Changes in the geographic distribution of the number of HIV cases and HIV prevalence among injecting drug users (IDUs) and non‐IDUs were examined. We also analysed changes in HIV prevalence among the broader DU population, and drug use‐related behaviours including types of drugs used, recent injecting and recent needle sharing in the context of the rapid scale‐up of DU sentinel sites and national harm reduction programmes. Findings: The HIV epidemic among China's DUs is still highly concentrated in five provinces. Here, HIV prevalence peaked at 30.3% [95% confidence interval (CI) = 28.6, 32.1] among IDUs in 1999, and then gradually decreased to 10.9% (95% CI = 10.6, 11.2) by 2011. We observed a rapid increase in the use of 'nightclub drugs' among DUs from 1.3% in 2004 to 24.4% in 2011. A decline in recent needle sharing among current IDU from 19.5% (95% CI = 19.4, 19.6) in 2006 to 11.3% (95% CI = 11.2, 11.4) in 2011 was found to be correlated with the rapid scale‐up of methadone maintenance treatment (MMT; r (4)  = −0.94, P  = 0.003) harm reduction efforts. Conclusions: While HIV prevalence and needle sharing among current injecting drug users in China have declined dramatically and are correlated with the scale‐up of national harm reduction efforts, the recent, rapid increased use of 'nightclub drugs' presents a new challenge.